2018
DOI: 10.1002/mde.2977
|View full text |Cite
|
Sign up to set email alerts
|

Returns on different types of investment in the global pharmaceutical industry

Abstract: Using stock market data of 10,550 publicly listed companies between 1987 and 2012, we study the marginal returns on investment for a large sample of pharmaceutical firms and compare them with returns on investment of firms from other industries. We also disentangle effects of different types of investments on total returns, namely, investment in advertising, research and development (R&D), fixed capital, and acquisitions. Our results suggest that the return of pharmaceutical companies on total investments is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Large facilities and costly machinery are necessary for drug production, along with a level of high R&D investment, indicating an economics of scale of the large existing company [20]. Approximately 7.1% of pharmaceutical companies' upfront R&D costs were made between 1987 and 2012 [21]. Moreover, the industry has been experiencing increasing regulatory requirements as well as the complexity of supply chain and biopharma operations, showing that early players in the industry are well-positioned to have a competitive advantage by overcoming legal barriers and seeking stable suppliers [22].…”
Section: Threats Of New Entrantsmentioning
confidence: 99%
“…Large facilities and costly machinery are necessary for drug production, along with a level of high R&D investment, indicating an economics of scale of the large existing company [20]. Approximately 7.1% of pharmaceutical companies' upfront R&D costs were made between 1987 and 2012 [21]. Moreover, the industry has been experiencing increasing regulatory requirements as well as the complexity of supply chain and biopharma operations, showing that early players in the industry are well-positioned to have a competitive advantage by overcoming legal barriers and seeking stable suppliers [22].…”
Section: Threats Of New Entrantsmentioning
confidence: 99%
“…Several studies have examined the association between R&D investments and various firm characteristics like profitability in the pharmaceutical industry (Pal & Nandy, 2019;Rao, 2020;Romasanta, van der Sijde, & van Muijlwijk-Koezen, 2020), financial performance (Nandy, 2020;Sharma, 2012), and equity returns (Mahlich & Yurtoglu, 2019). They claim that R&D expenses significantly impact on firm's profitability, financial performance, and stock returns.…”
Section: Randd Investment and Firm Factor Characteristicsmentioning
confidence: 99%
“…In parallel to the decreasing productivity, returns of investments in the pharmaceutical industry have dropped, a recent study found, analysing global stock market data from 1987 to 2012 [7]. In the second half of the observation period European pharmaceutical firms could not even earn their cost of capital and were actually destroying economic value, i.e.…”
Section: Introductionmentioning
confidence: 99%